PENGELOLAAN ARSIP DINAMIS INAKTIF DI KOMISI PEMILIHAN UMUM KABUPATEN SLEMAN - , IRFAN RAMDHANI W; , Drs. Burhanudin Dwi Rokhmatun ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Inactive records management are activities conducted on the inactive records, ranging from record removal of the central file to the record center to maintenance and care of inactive record in the records center. This final asigment explores the inactive records management system that is in Komisi Pemilihan Umum Sleman. Data collection methods using interviews, observations, participate in the process of inactive records managenment, and gather additional theories from library collection. This methods are used to obtain the data correctly and accurately. The conclusion of this final asigment, Komisi Pemilihan Umum has not done well managing inactive record. In managing their records are still there are many problems, such as limited equipment , the absence of processing and lack of archivist that exist in Komisi Pemilihan Umum.